Analysis of Blood Glucose using autoanalyzer Chemistry, Photometer, and Point of Care Testing (POCT) - Siti Zaetun; Baiq Tami Ariyanti; Lalu Srigede (Jurnal Riset Kesehatan, 2014)
Glucose levels in the blood can be checked using a variety of devices such as chemistry autoanalyzer (A15), photometer (Humalyzer 3000), and point of care testing (Gluco M). The problems that will be answered in this study is whether there are differences in the results of blood glucose levels using a chemistry autoanalyzer, photometer, and POCT. This study is a cross sectional study experimental. Glucose levels are checked glucose levels while using venous blood samples and can be checked using a chemistry autoanalyzer, photometer, and POCT. Based on the results of research conducted found a mean value of blood glucose levels using a chemistry autoanalyzer was 312.73 mg / dl, the photometer at 294 mg / dl, and POCT was 276.07 mg / dl. The results of the analysis showed no significant difference is p = 0.232 ˃ α (0.05).